2011
DOI: 10.12659/msm.881924
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin reuptake inhibitor antidepressants (SSRIs) against atherosclerosis

Abstract: SummarySelective serotonin reuptake inhibitors (SSRIs) are a class of drug widely used for treatment of mood disorders, including depression and cardiovascular disease. A search for related articles in the PubMed database was attempted. It covered studies, reports, reviews and editorials of the last 5 years.Pro-inflammatory cytokines, such as TNF-α, IL-1 and IL-6, stimulate central serotonin (5-HT) neurotransmission and are over-expressed in depression, which has been linked with hypothalamic-pituitary-adrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 90 publications
(117 reference statements)
1
40
0
Order By: Relevance
“…Since our previous studies with SSRIs such as escitalopram and sertraline (Bah et al, 2011;Wann et al, 2009) have shown no effect on infarct size, we hypothesized that its beneficial action is mainly related to inhibition of norepinephrine re-uptake rather than serotonin. Indeed, even though SSRIs can decrease platelet activation and the development of coronary heart disease (Wozniak et al, 2011) and reduce MI risk in the long-term (Kimmel et al, 2011), no data prove that SSRIs can reduce MI size, even our own (Bah et al, 2011;Wann et al, 2009). Richardt et al (2006), however, have reported that desipramine, a tricyclic antidepressant with norepinephrine uptake inhibition properties, has a dose-related cardioprotective effect on MI size.…”
Section: Discussionmentioning
confidence: 84%
“…Since our previous studies with SSRIs such as escitalopram and sertraline (Bah et al, 2011;Wann et al, 2009) have shown no effect on infarct size, we hypothesized that its beneficial action is mainly related to inhibition of norepinephrine re-uptake rather than serotonin. Indeed, even though SSRIs can decrease platelet activation and the development of coronary heart disease (Wozniak et al, 2011) and reduce MI risk in the long-term (Kimmel et al, 2011), no data prove that SSRIs can reduce MI size, even our own (Bah et al, 2011;Wann et al, 2009). Richardt et al (2006), however, have reported that desipramine, a tricyclic antidepressant with norepinephrine uptake inhibition properties, has a dose-related cardioprotective effect on MI size.…”
Section: Discussionmentioning
confidence: 84%
“…Some have gone so far as to recommend SSRIs to inhibit atherosclerosis progression (Wozniak et al, 2011). These recommendations stem from evidence of increased cardiovascular risk factors in depression such as arrhythmias, platelet reactivity, proinflammatory processes, cortisol concentrations, and low high-density lipoprotein cholesterol (HDLC) concentrations in women (Carney et al, 2002; Shively et al, 2009; Fantidis, 2010; Tedders et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CAMs were previously shown to be altered in placental disease (i.e., pre‐eclampsia and villitis) and have a time‐dependent effect in atherosclerosis, with each CAM molecule being unique . Further, studies have suggested a protective role of SSRIs in atherosclerosis, primarily thought to occur from SSRIs inducing production of pro‐inflammatory cytokines . Based on these results, the authors suggest that CAM modulation may play a partial role in SSRI‐induced protection against atherosclerosis, though further experimentation in vivo would be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Studies evaluating using these drugs during pregnancy did not occur until nearly a decade after the drugs were approved, with studies focusing on neonatal outcomes . Since then, studies have shown SSRIs induce the intended neurological effects, but also side effects on other tissues, including neurodevelopmental effects, cardiovascular‐related effects, effects on endothelial cells (ECs), and effects on the placenta itself and downstream fetal tissue . As it is widely accepted that SSRIs readily pass through the placenta and can impact fetal development, studies related to the role of the placenta and drug‐induced effects on the BPB have become increasing important .…”
Section: Introductionmentioning
confidence: 99%